Komposisi Proksimat dan Profil Mineral Tulang dan Sisik Ikan Papuyu (Anabas testudineus) - Sukma Sukma; Andi Mismawati; Bagus Fajar Pamungkas; Seftylia Diachanty; Ita Zuraida (Media Teknologi Hasil Perikanan, 2022)
Papuyu fish (Anabas testudineus) or also known as betok fish is a native Indonesian fish that is scattered in some area of freshwater such as in Kalimantan, Sumatra and Java. Information about the chemical characteristics of the bones and scales is currently limited. This study aims to determine the proximate composition and mineral profiles of the bones and scales of papuyu fish. The characteristics observed including the percentage of non edible portion, pH, proximate and minerals. Research data are presented in mean and standard deviation values as well as in table and histogram formats. Proximate analysis includes moisture content, ash, fat and protein, whereas analysis of mineral content including calcium, phosphorus, zinc, iron, potassium and sodium. The proportion of fish bone and scales are presented in percentage which have percentation of both bones of 1.67% and scale of 0.67%. The proximate values of papuyu fish bones in wet basis include the water content of 10.07%, ash content of 32.28%, fat 4.42% and protein content of 50.26%. The proximate values of papuyu fish scale in wet basis include the water content of 9.21%, ash content of 31.74%, fat of 3.49% and protein of 49.29%. The minerals profiles of the bone such as calcium, iron, potassium and sodium are higher than mineral from scale.Keyword:     Anabas testudineus, bone, scale, proximate, mineral profile. Ikan papuyu (Anabas testudineus) atau disebut juga ikan betok adalah jenis ikan asli Indonesia yang tersebar di beberapa perairan seperti Kalimantan, Sumatera dan Jawa. Informasi tentang karakteristik kimia tulang dan sisik ikan papuyu saat ini masih terbatas. Penelitian ini bertujuan untuk mengetahui karakteristik fisikokimia dan profil mineral tulang dan sisik ikan papuyu. Karakteristik yang diamati meliputi persentasi non edible portion, keasaman (pH), proksimat dan mineral. Data hasil penelitian disajikan dalam nilai rata-rata dan standar deviasi serta dalam format tabel dan histogram. Analisis proksimat meliputi kadar air, kadar abu, lemak dan protein, sedangkan analisis kandungan mineral meliputi kalsium, fosfor, seng, besi, kalium dan natrium. Nilai proporsi tulang ikan papuyu sebesar 1,67% dan sisik ikan papuyu sebesar 0,67%. Nilai proksimat tulang ikan dalam berat basah meliputi kadar air sebesar 10,07%, kadar abu 32,28%, lemak 4,42% dan kadar protein 50,26%. Nilai proksimat sisik ikan papuyu dalam berat basah meliputi kadar air 9,21%, kadar abu 31,74%, lemak 3,49% dan protein 49,29%. Kadar kalsium, besi, kalium dan natrium pada tulang ikan papayu lebih tinggi daripada bagian sisiknya.Kata kunci:       Anabas testudineus, tulang, sisik, proksimat, profil mineral.